Nonwoven

The nonwoven fabric with binder-induced spherical portions addresses fiber separation issues by reducing friction and enhancing smoothness, ensuring comfort despite abrasion.

JP7618470B2Active Publication Date: 2025-01-21KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021043814
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-01-21
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

Conventional nonwoven fabrics using heat-fusible short fibers experience fiber separation at fused intersections due to abrasion, leading to reduced smoothness and potential skin irritation, which existing patents do not address.

Method used

A nonwoven fabric with a binder and thermoplastic fibers featuring spherical portions formed at fusion points, where the binder transforms into spherical shapes with specific diameter and sphericity ranges, reducing friction and maintaining smoothness.

Benefits of technology

The spherical portions reduce friction and improve smoothness even after abrasion, preventing skin irritation and maintaining a smooth texture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618470000002
    Figure 0007618470000002
  • Figure 0007618470000003
    Figure 0007618470000003
  • Figure 0007618470000004
    Figure 0007618470000004
Patent Text Reader

Abstract

To provide a nonwoven fabric configured not to reduce smoothness even when being subjected to abrasion, and with the abrasion, capable of improving the smoothness.SOLUTION: A nonwoven fabric including a binder and thermoplastic fibers and having fusion points between the fibers, includes spherical portions formed of the binder attached to the thermoplastic fibers on one surface side of the nonwoven fabric. The spherical portion has a diameter more than twice the fiber diameter of the thermoplastic fiber, has the sphericity of 3.0 μm or more and 30.0 μm or less, and has an area in which the number of the spherical portions per unit area is 10 pieces / mm2 and more and 35 pieces / mm2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nonwoven fabrics. [Background technology]

[0002] Nonwoven fabrics are used as components of absorbent articles, etc. Technologies have been developed to impart various functions to nonwoven fabrics.

[0003] For example, Patent Document 1 describes a technique for binding various particles, such as superabsorbent particles used in absorbent products, to the surface of fibers via a binder. Patent Document 2 describes a nonwoven fabric having a substrate having thermally adhesive fibers, standing fibers fixed to the substrate, and free fibers independent of the fibers constituting the substrate. The document also describes that the fibers constituting the substrate and the standing fibers are made of long fibers. Patent Document 3 describes a long-fiber nonwoven fabric having fused parts. The long-fiber nonwoven fabric has free fibers having one end fixed to the fused parts, and the free fibers include flat fibers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 8-500270 [Patent Document 2] JP 2016-065335 A [Patent Document 3] JP 2019-214812 A Summary of the Invention [Problem to be solved by the invention]

[0005] Conventionally, nonwoven fabrics using short fibers with a fiber length of 100 mm or less and heat-fusible fibers have portions where fiber intersections are fused (hereinafter, fused intersections). When such nonwoven fabrics are used, such as by being incorporated into absorbent articles, if they are rubbed against clothing or the skin, depending on the degree of the rub, the fibers may peel off from the fused intersections. In this case, the peeled fibers may become frayed, reducing the smoothness of the nonwoven fabric. The above-mentioned patent documents do not disclose such fraying of fibers or a solution to this problem.

[0006] In view of the above, the present invention relates to a nonwoven fabric for absorbent articles whose smoothness does not decrease even when abraded, and whose smoothness can be improved as a result of abrasion. [Means for solving the problem]

[0007] The present invention relates to a nonwoven fabric having a binder and thermoplastic fibers and having fusion points between the fibers, the thermoplastic fibers on one side of the nonwoven fabric have spherical portions made of the binder attached thereto, the spherical portions have a diameter twice or more the fiber diameter of the thermoplastic fibers and a sphericity of 3.0 μm or more and 30.0 μm or less, and the number of the spherical portions per unit area is 10 / mm 2 More than 35 pieces / mm 2 A nonwoven fabric for absorbent articles is provided, having the following regions: Effect of the Invention

[0008] The nonwoven fabric for absorbent articles of the present invention does not lose its smoothness even when abraded, and the smoothness can be improved as the fabric is abraded. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1A is a schematic diagram showing a state in which a binder is attached to the fusion points between fibers, FIG. 1B is a schematic diagram showing an example in which a nonwoven fabric is rubbed, causing the fibers to peel off from the fusion points shown in FIG. 1A and the binder to change into spherical portions, and FIG. 1C is a schematic diagram showing another example in which the binder changes into spherical portions. [Diagram 2] 11 is a photograph substituted for a drawing showing a specific example of a spherical portion. [Diagram 3] 13 is a photograph substituted for a drawing showing another specific example of a spherical portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, preferred embodiments of the nonwoven fabric for absorbent articles (hereinafter, simply referred to as nonwoven fabric) of the present invention will be described. The nonwoven fabric of the present invention has a binder and thermoplastic fibers, and has fusion points between fibers (fusion points at fiber intersections). The fusion points are the parts where the fibers are bonded to each other by fusion of a thermoplastic resin component at the contact points between the intersecting fibers. At least one fiber among the fibers at the fusion points is a thermoplastic fiber. The fusion points are formed by, for example, melting the surface of the thermoplastic fiber by heat treatment during the manufacturing process of the nonwoven fabric, and fusing the fibers together. For example, a thermal bonded nonwoven fabric is used as the nonwoven fabric of the present invention, and more specifically, an air-through nonwoven fabric is used.

[0011] The nonwoven fabric of the present invention, which has fusion points between fibers, can use fibers of various lengths. For a thermally bonded nonwoven fabric, the heat-fusible fibers preferably contain short fibers having a fiber length of 10 mm or more and 100 mm or less.

[0012] In the nonwoven fabric of the present invention, the binder is attached to the surface of the thermally adhesive fiber, including the surface of the fusion point between the fibers. The binder present on the surface of the fusion point between the fibers preferably covers the outer surface of the portion where the fibers cross and overlap.

[0013] The binder is a resin component different from the constituent fibers of the nonwoven fabric, and is fixed to the surface of the constituent fibers after the nonwoven fabric is made. For example, the binder can be sprayed onto one side of the nonwoven fabric by a spray or the like to fix it to the surface of the fusion points of the fiber intersections, etc. In this way, in the nonwoven fabric of the present invention, the binder is uniformly attached over the entire planar area of ​​the nonwoven fabric.

[0014] In the nonwoven fabric of the present invention, spherical portions made of a binder are attached to the heat-fusible fibers on one side of the nonwoven fabric. The spherical portions have a diameter at least twice the fiber diameter of the thermoplastic fibers and a sphericity of 3.0 μm or more and 30.0 μm or less. The nonwoven fabric of the present invention has a number of spherical portions per unit area of ​​10 / mm 2 More than 35 pieces / mm 2 When the nonwoven fabric of the present invention has the above-mentioned number of spherical portions with the above-mentioned diameter and sphericity per unit area, the frictional resistance between the skin and the surface of the nonwoven fabric can be suitably reduced, the feeling of a foreign body on the surface of the nonwoven fabric is suppressed, and the nonwoven fabric has an excellent smooth texture. From the viewpoint of smoothness, the spherical portion is preferably located on one surface of the nonwoven fabric. The spherical portion may be located on both surfaces of the nonwoven fabric, not limited to one surface of the front or back surface. As long as the above requirements are satisfied, it is not necessary for all of the binder attached to the nonwoven fabric of the present invention 1 to become spherical portions. In the nonwoven fabric of the present invention 1, it is preferable that some of the binder becomes spherical portions and some of the binder does not become spherical portions.

[0015] As described above, the "spherical portion" is a portion having a diameter twice or more the fiber diameter of the thermoplastic fiber and a three-dimensional spherical shape with a sphericity of 3.0 μm to 30.0 μm. "Sphericity" is a value that indicates the degree of three-dimensional sphericity as defined by JIS B1501. The smaller the sphericity, the closer the shape is to a sphere. By making the spherical portion 3.0 μm to 30.0 μm, the frictional resistance felt by the skin can be reduced. In addition, by making the spherical portion have a diameter twice or more the fiber diameter of the thermoplastic fiber, the sphere can be felt as a touch.

[0016] The sphericity is preferably 25.3 μm or less, more preferably 20.0 μm or less, from the viewpoint of reducing the frictional resistance felt by the skin, and is preferably 5.0 μm or more, more preferably 8.0 μm or more, from the viewpoint of increasing the contact area between the binder and the fusion point of the fibers and suppressing peeling between the fibers. In addition, from the viewpoint of reducing the frictional resistance felt by the skin by making the spherical portions larger than the peeled shape of the fibers, the diameter of the spherical portions is preferably 2.2 times or more, and more preferably 2.5 times or more, the fiber diameter of the thermoplastic fibers. From the viewpoint of suppressing unevenness on the surface of the nonwoven fabric and maintaining a smooth texture, the diameter of the spherical portions is preferably 4.0 times or less, and more preferably 3.7 times or less, the fiber diameter of the thermoplastic fibers.

[0017] In order to further enhance the smoothness of the nonwoven fabric of the present invention, the number of spherical parts per unit area in the region having the spherical parts is set to 15 / mm 2 More preferably, 20 pieces / mm 2 From the viewpoint of reducing the unevenness of the surface of the nonwoven fabric and maintaining a smooth texture, the number of spherical parts per unit area in the region having the spherical parts is preferably 33 / mm. 2 Preferably less than 30 pieces / mm 2 The following is more preferred:

[0018] (Method of measuring the number of spherical parts per unit area and sphericity) (1) With the sample resting with the scratched surface facing up, images are taken at 500x magnification using a digital microscope VHX-900 (manufactured by Keyence Corporation) at angles of 60 degrees and 120 degrees to the sample. Based on this, rc (maximum radius within the limiting circle) and rs (minimum radius within the limiting circle) are measured, and the three-dimensional sphericity is calculated. (2) Draw a 0.5 mm x 0.5 mm square on the observed image as a reference line. Count the number of spherical parts within the square based on the method specified in JIS B1501. Calculate the unit area (1 mm2) from the number of spherical parts measured. 2 ) per unit. (3) Calculate the average sphericity of the 10 spherical portions mentioned above and use this as the measurement data.

[0019] (Method for measuring the ratio of the diameter of the bulb to the diameter of the thermoplastic fiber) For the spherical portion obtained from the observation image in the measurement of sphericity, the minimum diameter within the limiting circle is measured, and this is divided by the fiber diameter obtained from the observation image. Ten measurements are taken, and the average is used as the measurement data.

[0020] The number of spherical parts per unit area is 10 / mm 2 More than 35 pieces / mm 2 The area on the nonwoven fabric plane described below is preferably at least the area of ​​the nonwoven fabric of the present invention that comes into contact with the skin. This area is at least 100 mm 2 More than 500mm is preferable. 2 More than 1000m is preferable. 2 It is more preferable that the entire plane of the nonwoven fabric of the present invention is the above-mentioned region.

[0021] The "spherical portion" is a result of the binder adhering to the surface of the thermoplastic fiber being changed by abrasion, and has the above-mentioned three-dimensional spherical shape that the binder does not have before being subjected to abrasion.

[0022] By generating such "spherical portions" by rubbing, the frictional resistance of the surface of the nonwoven fabric of the present invention after the "spherical portions" are provided is reduced, and smoothness is improved. As a result, even if the fibers of the nonwoven fabric of the present invention are peeled off from the fusion points between the fibers by rubbing, the presence of the spherical portions reduces irritation to the skin due to roughness, and smoothness is improved. Furthermore, even after spherical portions are generated by rubbing once, the remaining binder can be converted into spherical portions by further rubbing, so that smoothness can be further improved by rubbing.

[0023] Abrasion that can produce "spherical parts" is at least the abrasion shown in the following [Abrasion Conditions]. By applying abrasion that satisfies or exceeds these conditions, the binder on the surface of the heat-fusible fiber, especially the binder at the fusion points between the fibers, changes into the spherical parts defined above. In the area where abrasion has been applied, the number of the spherical parts per unit area is 10 pieces / mm 2 More than 35 pieces / mm2 The result is as follows.

[0024] [Rubbing conditions] (1) Cut out a measurement sample measuring 100 mm x 100 mm from the nonwoven fabric to be measured. (2) A disk (70 mm in diameter, 350 g) covered with a sheet having a surface friction coefficient of 0.4 to 0.6 is attached to a rotating shaft. The attachment position is 20 mm away from the center of the disk. Various types of sheets such as urethane foam, cloth, and paper can be used as the sheet, and urethane foam is preferable. For example, Malt Filter MF-30 (product name, thickness 5 mm, surface friction coefficient 0.508) manufactured by Inoac Corporation can be used. (3) Place the same sheet as above on the underside of the nonwoven fabric sample and fix it on the table. Place the disk on top of the nonwoven fabric. At this time, the only load applied to the nonwoven fabric is the weight of the disk. (4) Under this condition, rotate the rotating shaft to rotate the disk on the nonwoven fabric. The rotation is performed 15 times, with one set consisting of three rotations clockwise and three rotations counterclockwise. The rotation time for each set is 18 seconds.

[0025] The above-mentioned "abrasion conditions" are based on the assumption that the nonwoven fabric of the present invention will be subjected to abrasion during use when the nonwoven fabric is incorporated as a skin-contacting member in an absorbent article, etc. In reality, the nonwoven fabric of the present invention can be tolerated to be subjected to abrasion over a wider area during normal use.

[0026] The nonwoven fabric of the present invention has a binder and thermoplastic fibers and has fusion points between the fibers before it is subjected to abrasion, i.e., before the "spherical portions" are formed. Some of the binder is attached to the surface of the fusion points. As described above, the binder is still present in the nonwoven fabric of the present invention after it is subjected to abrasion and the "spherical portions" are formed.

[0027] The binder has an adhesive property that allows it to adhere to the fiber surface and not run off, but also has an elastic property that allows it to change into a rounded shape when rubbed. From this viewpoint, the binder is preferably a resin having a glass transition point of -40°C or more and 30°C or less. From the viewpoint of suppressing stickiness due to adhesion, the glass transition point of the binder is more preferably -30°C or more, and even more preferably -20°C or more. Moreover, from the viewpoint of generating elasticity that allows deformation into a spherical shape by rubbing, the glass transition point of the binder is more preferably 25°C or less, and even more preferably 20°C or less. The above glass transition point is measured from a DSC curve obtained by differential scanning calorimetry in accordance with JIS K 7121.

[0028] The content of the binder in the nonwoven fabric of the present invention is preferably not too high from the viewpoint of suppressing stickiness on the surface of the nonwoven fabric and enabling the change into spherical portions, and is preferably 12.0 g / m per unit area of ​​the nonwoven fabric. 2 Less than 6.0 g / m is preferred. 2 Less than 3.0 g / m is more preferable. 2 From the viewpoint of generating the aforementioned spherical portions in sufficient size and number, the content mass of the binder is preferably 0.5 g / m2 per unit area of ​​the nonwoven fabric. 2 More than 1.0 g / m is preferable. 2 More preferably, 1.5 g / m 2 The above is more preferable. In addition, the proportion of the binder on the fusion point is determined based on the unit area (1 mm 2 With respect to the number of fusion points per unit area, it is preferably 20% or more, more preferably 30% or more, and is preferably 50% or less.

[0029] The nonwoven fabric of the present invention has a structure in which the binder is sprayed onto the flat surface of the nonwoven fabric in the above-mentioned specific amount. Therefore, the nonwoven fabric of the present invention contains the binder, and in any area where abrasion is applied by contact with the skin, the nonwoven fabric is provided with the above-mentioned spherical portion by being subjected to abrasion. The magnitude of abrasion applied by contact with the skin is not limited to the magnitude of abrasion shown in the above-mentioned [Abrasion Conditions], and may be greater than the magnitude.

[0030] The basis weight of the nonwoven fabric of the present invention is 10 g / m2 from the viewpoint of maintaining the strength of the nonwoven fabric while containing a small amount of the binder. 2 More than 15g / m is preferable. 2 More preferably, 20 g / m 2 The basis weight of the nonwoven fabric of the present invention is more preferably 60 g / m2 from the viewpoint of providing flexibility. 2 Less than 50 g / m is preferable. 2 Less than 40 g / m is more preferable. 2 The following is even more preferred:

[0031] From the viewpoint of improving smoothness after being subjected to abrasion, it is preferable that the spherical portions adhere to the peeled surfaces of the fibers peeled off from the fusion points or to the surfaces of the fusion points remaining after peeling. The number of spherical parts present on the peeled surface of the peeled fiber or on the surface of the remaining fusion point after peeling is 15 / mm2 in terms of the number per unit area in the region having the spherical parts. 2 More than 20 pieces / mm is preferable. 2 The ratio of spherical parts present on the peeled surface of the peeled fibers or on the surface of the remaining fusion points after peeling is preferably 31 pieces / mm2 in terms of the number per unit area in the region having spherical parts, from the viewpoint of reducing the unevenness of the nonwoven fabric surface and maintaining a smooth texture. 2 Less than 25 pieces / mm is preferable. 2 The following is more preferred:

[0032] (Method for measuring spherical parts present on the peeled surface of peeled fibers or on the surface of remaining fusion points after peeling) The measurement can be performed in the same manner as described above (method of measuring the number of spherical portions per unit area and sphericity).

[0033] The above-mentioned "peeling" of fibers means that a part or all of the fused fibers are separated from the fusion point. It is not limited to the case where the fibers are separated from the fusion point without breakage, but includes various forms such as the surface part of the fiber being cut or torn, the surface part of the fiber being pulled out from the core part of the fiber, etc. For example, when a fusion point is formed at the intersection of two fibers and the fibers are peeled off from each other, both of the two fibers correspond to "peeled fibers". When a fusion point is formed at the intersection of three or more fibers and one of the fibers is peeled off, that one fiber is the "peeled fiber", and the fusion point between the remaining two or more fibers is the "remaining fusion point after peeling". Alternatively, the fibers may be partially cut and peeled off at the fusion point. For example, from a state where a fusion point is formed at the intersection of two fibers (a state where four fiber legs are apparently sticking out from the fusion point), a part of one fiber (one of the four fiber legs) may be cut and peeled off. In this case, the broken fiber part corresponds to the "peeled fiber", and the fusion points of the remaining three fiber legs correspond to the "remaining fusion points after peeling". The "peeled surface of the peeled fiber" refers to the portion of the fiber that was fused at the fusion point and is the surface of the fiber that is exposed by peeling.

[0034] The state where "the spherical portion is attached to the peeled surface of the fiber peeled from the fusion point or the surface of the remaining fusion point after peeling" refers to, for example, the following state: That is, the binder that was attached to the surface of the fusion point between the fibers is rubbed, and while changing into the spherical portion by becoming round, it is in a state where it migrates to "the peeled surface of the peeled fiber" and remains on "the surface of the remaining fusion point after peeling."

[0035] For example, as shown in FIG. 1(A), abrasion is applied from a state where the binder 3 is attached to the surface of the fusion point at the intersection of the core-sheath composite fiber (hereinafter simply referred to as fiber) 1 and 2. As a result, as shown in FIG. 1(B), the sheath portion (surface portion) 11 of fiber 1 comes off from the core portion 12 of the fiber, and the sheath portion 11 of fiber 1 remains fused to the portion that was the fusion point of fiber 2. The binder 3 changes to a spherical portion 41 and adheres to or covers this portion. At this time, the sheath portion 11 of fiber 1 is curled up together with the binder 3 at the portion that was the fusion point of fiber 2 and is covered by the spherical portion 41. For example, the spherical portion 41 shown in FIG. 2 is generated as this spherical portion 41. Or, as shown in FIG. 1(C), fiber 1 and fiber 2 are peeled off from the fusion point, and the binder 3 is separated by its elasticity and changes to a spherical portion 42 attached to fiber 1. A small amount of binder 31 remains on fiber 2. As this spherical portion 42, for example, one as shown in FIG. 3 is generated. Whether the state shown in Fig. 1(B) or the state shown in Fig. 1(C) is obtained largely depends on the glass transition point (Tg) of the binder. For example, in the above-mentioned preferred glass transition point (Tg) range, if the binder has a higher glass transition point (Tg), the binder will have stronger hardness than elasticity, and will tend to have a shape like that shown in Fig. 1(B). On the other hand, if the binder has a lower glass transition point (Tg), the binder will have stronger elasticity and will tend to have a shape like that shown in Fig. 1(C). From the viewpoint of improving the smoothness of the nonwoven fabric, it is more preferable that the nonwoven fabric of the present invention contains spherical portions 42 in the form shown in Fig. 1(C). From the viewpoint of favorably forming spherical portions 42 in this form and preventing the smoothness from being deteriorated due to the adhesiveness of the binder itself, the glass transition point of the binder is preferably -20°C or more and 20°C or less.

[0036] The thermoplastic fibers and binder constituting the nonwoven fabric of the present invention will now be described.

[0037] The thermoplastic fiber may be any fiber that is commonly used as a material for nonwoven fabrics without any particular limitations. For example, it may be a fiber made of a single resin component or a composite fiber made of multiple resin components. The composite fiber may have, for example, a core-sheath structure or a side-by-side structure. When using composite fibers containing a low melting point component and a high melting point component as the thermoplastic fiber (for example, composite fibers having a sheath-core structure in which the sheath is a low melting point component and the core is a high melting point component), the temperature of the hot air blown onto the fiber web in the manufacturing process is preferably equal to or higher than the melting point of the low melting point component and lower than the melting point of the high melting point component. More preferably, the temperature is equal to or higher than the melting point of the low melting point component and 10°C lower than the melting point of the high melting point component, and even more preferably, the temperature is 5°C or higher than the melting point of the low melting point component and 20°C or lower than the melting point of the high melting point component. A specific example of a composite fiber having a sheath-core structure in which the sheath is a low melting point component and the core is a high melting point component is a composite fiber having a sheath-core structure in which the sheath is a polyethylene resin (hereinafter also referred to as PE) and the core is a polyethylene terephthalate resin (hereinafter also referred to as PET).

[0038] Various binders can be used, including, for example, acrylic resins, ester resins, vinyl acetate resins, styrene resins, vinyl acetate-ethylene resins, and styrene-butadiene rubber. In particular, from the viewpoint of favorably generating spherical portions by rubbing, it is preferable for the material to have the above-mentioned glass transition point. Examples include acrylic resins and styrene-butadiene rubber.

[0039] Such a nonwoven fabric of the present invention can be used for various applications, for example, in absorbent articles. An absorbent article typically has a top sheet arranged on the skin contact side, a back sheet arranged on the non-skin contact side, and an absorbent sandwiched between the top sheet and the back sheet. In such absorbent articles, the nonwoven fabric of the present invention can be suitably used as a top sheet of absorbent articles such as diapers, sanitary napkins, panty liners, and urine absorption pads. Furthermore, it can also be used as a sheet in the gather part, an exterior sheet, or a sheet in the wing part of an absorbent article. The nonwoven fabric of the present invention can also be used as a component of an eye mask or a mask. EXAMPLES

[0040] The present invention will be described in more detail below based on examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are all based on mass unless otherwise specified. In the following tables, "-" means that the item does not have a corresponding value, etc.

[0041] Example 1 (1) Preparation of raw nonwoven fabric A raw nonwoven fabric was produced by the air-through method using the thermoplastic composite fibers having a core-sheath structure shown in Table 1. The size of the raw nonwoven fabric was 100 mm x 100 mm. (2) Preparation of binder coating solution A binder solution with a solid content of about 50% was mixed with deionized water at 90% by mass to prepare a binder coating solution. The binder solution used had a glass transition point of 10°C (Boncoat AC-501 (product name) manufactured by DIC Corporation. Ingredients: acrylic resin 59.4% by mass, water 35-45% by mass, ammonia (containing water) less than 1% by mass, others less than 1% by mass). The binder solution had a pH of 7.9 and a viscosity of 401 mPa·s. (3) Spraying the binder coating liquid Next, the binder coating solution was evenly applied to the raw nonwoven fabric from above by spraying. Then, it was dried for 5 minutes at 120°C in an electric dryer. The coating amount of the solid content of the binder solution was as shown in Table 1. This was measured by the change in the mass of the nonwoven fabric before and after the binder coating. In this way, nonwoven fabric sample A1 of Example 1 having the basis weight shown in Table 1 was produced. (4) Applying abrasion Nonwoven fabric sample A1 was subjected to rubbing under the above-mentioned [Rubbing conditions] to prepare a nonwoven fabric sample A11 after rubbing.

[0042] Example 2 Nonwoven fabric sample A2 of Example 2 and nonwoven fabric sample A21 after rubbing were prepared in the same manner as in Example 1, except that the coating amount of the solid content of the binder solution and the basis weight of the nonwoven fabric sample were as shown in Table 1.

[0043] Example 3 Nonwoven fabric sample A3 of Example 3 and nonwoven fabric sample A31 after abrasion were prepared in the same manner as in Example 1, except that the fibers were as shown in Table 1.

[0044] Example 4 Nonwoven fabric sample A4 and nonwoven fabric sample A41 after rubbing were prepared in Example 4 in the same manner as in Example 1, except that a binder solution with a glass transition point of the solid content of -40°C (Boncoat AB-886 (product name) manufactured by DIC Corporation; components: 50.8 mass % acrylic resin, 45-55 mass % water, less than 1 mass % n-butyl acrylate, less than 1 mass % isopropyl alcohol, less than 1 mass % others) was used. The binder solution had a pH of 6.6 and a viscosity of 40 mPa s.

[0045] Comparative Example 1 Nonwoven fabric sample C1 and nonwoven fabric sample C11 after abrasion were prepared in the same manner as in Example 1, except that no binder was sprayed.

[0046] Comparative Example 2 Nonwoven fabric sample C2 of Comparative Example 2 and nonwoven fabric sample C21 after rubbing were prepared in the same manner as in Example 4, except that the application amount of the solid content of the binder solution and the basis weight of the nonwoven fabric sample were as shown in Table 1.

[0047] Comparative Example 3 Nonwoven fabric sample C3 and nonwoven fabric sample C31 after rubbing in Comparative Example 3 were prepared in the same manner as in Example 1, except that a binder solution with a glass transition point of the solid content of 30°C (DICFINE AJ-1820 (product name) manufactured by DIC Corporation; components: 50-60 mass % water, 44.5 mass % acrylic resin, less than 1 mass % ammonia (containing water), less than 1 mass % others) was used. The binder solution had a pH of 6.1 and a viscosity of 588 mPa s.

[0048] Comparative Example 4 Nonwoven fabric sample C4 and nonwoven fabric sample C41 after rubbing in Comparative Example 4 were prepared in the same manner as in Example 1, except that a binder solution having a glass transition point of -40°C (Polysol AT-741 (product name) manufactured by Showa Denko K.K.; acrylic resin 56.5% by mass, components: water 43.5% by mass) was used as the binder solution. The binder solution had a pH of 7.9 and a viscosity of 4900 mPa s.

[0049] (Reference example) A reference example nonwoven fabric sample R1 and a nonwoven fabric sample R11 after rubbing were prepared using thermoplastic composite fibers having a core-sheath structure shown in Table 1 in the same manner as in Example 1 of the aforementioned Patent Document 3, without applying a binder solution, and having flat fibers as free fibers and basis weights shown in Table 1. Note that there were no spherical portions in the reference example, and the numerical values ​​of the spherical portions shown in Table 1 below are those related to the flat fibers.

[0050] For each of the nonwoven fabric samples in the above Examples, Comparative Examples, and Reference Examples, measurements were carried out based on the above (Method of measuring the number of spherical portions per unit area and sphericity) and (Method of measuring the ratio of the diameter of the spherical portion to the fiber diameter of the thermoplastic fiber).

[0051] For each of the nonwoven fabric samples in the above Examples and Comparative Examples, the various values ​​were measured on the side that had been rubbed based on the above-mentioned (Method of measuring the number of spherical portions per unit area and sphericity) and (Method of measuring the ratio of the diameter of the spherical portions to the fiber diameter of the thermoplastic fiber).

[0052] Furthermore, for each of the nonwoven fabric samples of the above Examples and Comparative Examples, the MMD (mean deviation of the coefficient of friction) was measured as an index of the smoothness of the nonwoven fabric surface. [Method of measuring MMD (mean coefficient of friction variation)] The mean coefficient of friction (MMD) of the nonwoven fabric surface was measured using an automatic surface tester (KES-FB4-A-SE, manufactured by Kato Tech Co., Ltd.) The surface to be measured was the side to which the abrasion described above in [Abrasion conditions] was applied. The test specimen was attached to a smooth, flat metal test stand. The contact surface of the contactor was pressed against the test specimen with a force of 49 cN, and the test specimen was moved horizontally 2 cm at a constant speed of 0.1 cm / sec. A uniaxial tension of 19.6 cN / cm was applied to the test specimen. The contactor was made of 20 pieces of 0.5 mm diameter piano wire bent into a U-shape with a width of 10 mm, and the contact surface was pressed against the test specimen with a force of 49 cN using a weight. The measured value of the mean deviation of the friction coefficient is expressed as the MMD value. This measurement was performed in both the MD (machine direction, or the direction parallel to one side of the test piece) and the CD (direction perpendicular to the MD), and the average value was calculated using the following formula (S1), which was used as the average deviation of the friction coefficient. Friction coefficient mean deviation = {(MMD MD 2 +MMD CD 2 ) / 2} 1 / 2 (S1) The average deviation of the friction coefficient indicates the degree of variation in friction, with a smaller value indicating a higher degree of smoothness when touched by hand.

[0053] [Table 1]

[0054] As shown in Table 1, the nonwoven fabric samples of Examples 1 to 4 contained a binder, and by rubbing, spherical parts having a diameter twice or more the fiber diameter of the constituent fibers and a sphericity of 3.0 μm to 30.0 μm were generated at a rate of 10 pieces / mm2 per unit area. 2 More than 35 pieces / mm 2The nonwoven fabric samples of Examples 1 to 4 had a high smoothness not found in the nonwoven fabric samples of Comparative Examples 1 to 4 both before and after rubbing, and the smoothness was improved by rubbing compared to the nonwoven fabric samples before rubbing. In this respect, the nonwoven fabric sample of Comparative Example 2 had an excessive amount of binder, so the stickiness of the binder itself was dominant over the fraying prevention effect of the spherical parts, and the smoothness (MMD) value was poor. The nonwoven fabric sample of Comparative Example 3 had a binder with a high glass transition point and a hard binder, and after rubbing, the binder broke and became sharp, so the spherical parts disappeared and the smoothness (MMD) was also deteriorated. The nonwoven fabric sample of Comparative Example 4 had a high adhesiveness of the binder, which formed a film between the fibers, so that the spherical parts were not formed, and the smoothness (MMD) value was poor both before and after rubbing. [Explanation of symbols]

[0055] 1, 2 Core-sheath composite fiber 3, 31 Binder 11 Fiber sheath (surface part) 12 Core of the fiber 41, 42 Spherical part

Claims

1. A nonwoven fabric having a binder and thermoplastic fibers and having fusion points between the fibers, the thermoplastic fibers on one side of the nonwoven fabric have spherical portions made of the binder attached to the peeled surfaces of the fibers peeled from the fusion points or to the surfaces of the fusion points remaining after peeling; The spherical portion has a diameter twice or more the fiber diameter of the thermoplastic fiber and a sphericity of 3.0 μm or more and 30.0 μm or less, The number of the spherical portions per unit area is 10 / mm 2 35 pieces / mm or more 2 A nonwoven fabric for absorbent articles having the following areas:

2. A nonwoven fabric having a binder and thermoplastic fibers and having fusion points between the fibers, The binder is attached to the surface of the fusion point, When the fibers are rubbed under the following [Rubbing Conditions], the binder is transformed into the spherical portions described in claim 1 on the peeled surface of the fibers peeled from the fusion points or on the surface of the remaining fusion points after peeling, and the number of the spherical portions per unit area in the rubbed area is 10 / mm 2 35 pieces / mm or more 2 A nonwoven fabric for absorbent articles comprising: [Rubbing conditions] (1) A measurement sample measuring 100 mm x 100 mm is cut out from the nonwoven fabric to be measured. (2) A disk (70 mm in diameter, 350 g) covered with a sheet whose surface has a friction coefficient of 0.4 to 0.6 is attached to a rotating shaft at a position 20 mm away from the center of the disk. (3) Place the same sheet as above on the bottom surface of the nonwoven fabric sample and fix it on a table. Place the disk on top of the nonwoven fabric. At this time, the load applied to the nonwoven fabric is only the weight of the disk. (4) In this state, the rotating shaft is rotated to rotate the disk on the nonwoven fabric. The rotation is performed for 15 sets, with one set consisting of three rotations clockwise and three rotations counterclockwise. The rotation time for each set is 18 seconds.

3. The nonwoven fabric for absorbent articles according to claim 1 or 2, wherein the thermoplastic fibers include staple fibers.

4. The nonwoven fabric for absorbent articles according to any one of claims 1 to 3, wherein the thermoplastic fiber is a bicomponent fiber.

5. The nonwoven fabric for absorbent articles according to any one of claims 1 to 4, wherein the thermoplastic fibers have a core-sheath structure.

6. The nonwoven fabric for absorbent articles according to any one of claims 1 to 5, wherein the binder is a resin having a glass transition point of -40°C or more and 30°C or less.

7. The nonwoven fabric for absorbent articles according to claim 1, wherein the mass content of the binder in the nonwoven fabric is 0.5 g / m 2 or more and 12.0 g / m 2 or less.

8. An absorbent article comprising the nonwoven fabric according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Binder composition for nonwoven fabric and production of nonwoven fabric

    JP1995238451A

  • Particle bonding to fibers

    JP1996500270A

  • Female member for hook-and-loop fastener and manufacture thereof

    JP1998304909A

  • Non-woven fabric and manufacturing method thereof

    JP2016065335A

  • Nonwoven fabric and manufacturing method thereof and absorbent article

    JP2016108714A